Green Accounting, CSR, Sustainability Disclosure dan ROA - Sukiyaningsih, Tri Wahyuni; Hasanah, Ade Nahdiatul (Ekonomis: Journal of Economics and Business, 2024)
A company image is needed in building a business, it cannot be denied that an image can effect all aspect, one of which is financial performance. This financial performance is greatly influenced by economic aspect. One of then is green accounting and CSR. Companies must also be abale to survive in the face of all economic, social, and enviromental conditions. This research focuses on quatitative approach with secondary data from the compass 100 index from 2020-2023. The sample used was 96 companies tahe has been identified and classified according to predetermined criteria. Statistical data processing uses smart PLS4 to produce structural analysis and measurement in the form of path analysis, FIT model, R-square and hypothesis teating the bootstrapping method. Based on the result of the, green accounting has on effect of sustainbility report and financial performance, green accounting has on effect of financial performance, CSR has on effect of sustaibility report, but corporate social responsibility has no effect of financial performance and sustainbility report has on effect to financial performance